(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The swift progression of technology has revolutionized the global scenario. The changes brought by the digital revolution have transformed the legal arena, particularly regarding the utilization of digital evidence in court proceedings. This paper investigates the legal framework governing the admissibility, reliability, and challenges of digital evidence in courts functioning in India. It delves into the statutory provisions outlined in the Information Technology Act, 2000, and related amendments that form the foundation of digital evidence admissibility, including the Indian Evidence Act, 1872. The paper also explores practical issues faced by legal practitioners in acquiring, preserving, and presenting digital evidence, which includes challenges faced due to data tampering and the evolving nature of cybercrimes. Furthermore, the paper discusses the need for more legal reforms to match the implications of emerging technologies. In conclusion, the specific objective of the paper is to highlight the importance of strategies and foresight for the effective utilization of digital evidence in Indian courts to ensure that the principles of justice and fairness are intact in the digital age.